Photocatalytic Degradation of Methylene Blue from Aqueous Medium onto Perlite-Based Geopolymer - Hamid Saufi; Marouane El Alouani; Saliha Alehyen; Mohammed El Achouri; Jilali Aride; M’hamed Taibi (International Journal of Chemical Engineering)
In this work, geopolymer synthesized with perlite and an alkaline activator medium was evaluated as a new adsorbent and photocatalyst for degradation of methylene blue (MB) dye from an aqueous medium. The functional group, the structure, and the morphology of the raw and the synthesized materials were characterized using FT-IR, XRD, and SEM analysis. The degradation of MB in the contaminated solution was examined using the spectrophotometric technique. Several analysis methods revealed the formation of the aluminosilicate gel after the geopolymerization reaction. The kinetics data with UV and without UV irradiations were well fitted with the pseudo-second-order equation. The results indicated that the degradation efficiency of cationic dye by perlite-based geopolymer without and with UV was up to 88.94% and 97.87% in 4 hours, respectively. The degradation efficiencies of methylene blue are in the following order: perlite-based geopolymer under UV irradiations is greater than perlite-based geopolymer without UV irradiations that is larger than UV irradiations. The overall experimental results suggested that the new elaborated material with synergetic adsorption and photocatalytic activities has a great potential for the treatment of water contaminated by hazardous substances.